The effects of customised brainwave music on orofacial pain induced by orthodontic tooth movement. (1st August 2016) - Huang, R; Wang, J; Wu, D; Long, H; Yang, X; Liu, H; Gao, X; Zhao, R; Lai, W
Abstract : Objectives: To evaluate the effects of listening to brainwave music (BWM), which is composed by individual electroencephalogram (EEG) signals, in relieving orthodontic pain, compared to cognitive behavioural therapy (CBT), an established psychotherapy in pain management. Methods: Thirty‐six participants matched for age, gender and anxiety/pain levels were randomly assigned to the BWM group ( n = 12), the CBT group ( n = 12) or the control group ( n = 12). Baseline resting EEG data were fabricated into BWM for the BWM group. EEG signals and pain perception [assessed by visual analogue scale (VAS)] of participants were recorded for the first week after orthodontic appliances placement. EEG data were analysed by multiple approaches. Results: Brainwave music and CBT groups presented significantly lower pain perception than the control group on days 1–4. According to EEG analysis outcomes, the BWM group showed improved functional connectivity among different brain regions, lower EEG complexity and enhanced power in theta and alpha bands, compared to CBT and control groups, especially on day 2. Differences were clustered in the prefrontal, frontal, parietal and occipital regions, whilst the EEG parameters had negligible linear association with VAS scores. Conclusions: Brainwave music is effective in controlling orthodontic pain, possibly via restoring functional connectivity and brain regularity influenced by pain.